Genetic Diversity of Indonesian Bacterial Leaf Blight Isolate (Xanthomonas oryzae pv. oryzae) Core Collection based on the VNTR and avrXa7 Molecular Markers - Yuriyah, Siti; Utami, Dwinita Wikan (Makara Journal of Science, 2015)
Bacterial leaf blight (BLB) is one of the major diseases in rice caused by Xanthomonas oryzae pv. oryzae. This study aimed to identify and analyze the genetic diversity of 18 BLB isolates that consist of 7 races and 11 haplotypes from various locations in Indonesia. The genetic diversity analysis was conducted on the basis of the VNTR (Variable Number of Tandem Repeat) markers and the avrxa7 gene marker. The banding pattern of the amplification product was made into binary data as input for the construction of a dendogram. Based on the dendogram, three X. oryzae pv. oryzae genotype groups with different virulence levels were formed. The VII (IXO80_021) race of X. oryzae pv. oryzae genotype group I and the VIII-A (IXO 80_024) race of genotype group II were avirulent, whereas the races and haplotypes of genotype group III were virulent.